Indonesia’s Political Colours: From the New Order to Joko Widodo - Sibarani, Rifka (FISIP Universitas Atma Jaya Yogyakarta, 2018)
This study aims to examine the meaning behind the political colours in Indonesia. It uses Roland Barthes’ semiotics analysis. The results show that yellow is identified with the power of Golongan Karya Party which means oligarch wealth; red symbolises the intertwine association of the communism history and the labour movement in Indonesia with PDI Perjuangan; blue symbolises the values of patriotism and neoliberalist agenda for Susilo Bambang Yudhoyono: whereas the combination of red-white-black of Joko Widodo’s plaid shirt symbolises political progressiveness.